Improving the Impact on Human Capital Development through Child Grant in Nepal - Dhakal, Thakur; Kandel, Tara; Kafle, Puskar (Journal of Social Protection, 2023)
The Government of Nepal has made significant achievements in expanding social protection during the last two and half decades. Child grant is one of the entitlements provisioned by the government to enhance nutritional status and overall wellbeing of children which is universal in 25 districts of Nepal. This paper aims to explore how child grant can contribute to human capital development and its rationalization in scaling up throughout the nation. Furthermore, the paper suggests the possible fiscal spaces to leverage resources to expand universal child grant. Investments in early childhood development and nutrition can help break inter-generational cycles of poverty and promote equitable development by providing children with the resources they need to reach their full potential. This, in turn, can lead to increased economic productivity and social well-being. Also, the paper urge to increase the investment in children through universal child grant to serve the aging society in future.